An optimization‐based web application for synthesis and analysis of biomass‐to‐fuel strategies. (16th October 2017) - Ng, Rex T. L.; Patchin, Sean; Wu, Wenzhao; Sheth, Nihar; Maravelias, Christos T.
Abstract: We develop an optimization‐based web application for assessing biomass‐to‐fuels strategies based on the Biomass Utilization Superstructure (BUS) framework. This web application allows researchers with limited knowledge of optimization to assess different technologies employed at different strategies and identify the major cost drivers. The user must only provide the necessary parameters and create an optimization run after identifying the question to be addressed and the assessment metric. The web application generates visual representations of the results once the optimal solution is obtained. Finally, we demonstrate the applicability of the web application through an example. © 2017 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.